2024
DOI: 10.3390/world5010003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potentials of Halophytes in Addressing Climate Change-Related Issues: A Synthesis of Their Biological, Environmental, and Socioeconomic Aspects

Abdul Hameed,
Sadiq Hussain,
Aysha Rasheed
et al.

Abstract: Halophytes are naturally salt-tolerant plants with immense potential to become alternate crops for saline lands. While their economic benefits have gained increasing attention, often, the roles of halophytes in addressing different climate change-related issues are overlooked. Halophytes can be a renewable resource for clean ‘carbon-neutral’ energy by serving as biofuel or biogas feedstock, help in the sequestration of rising CO2 as well as the phytoremediation of various pollutants, can be a good source of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 189 publications
0
0
0
Order By: Relevance
“…Notably, this finding aligns with a previous study that demonstrated approximately threefold variation in glasswort length based on salinity [43]. Hameed et al [44] reported that halophytes have the potential to be used as a sustainable source of food, fuel, feed, fiber, essential oil, and medicine. These hardy plants thrive in high-salinity and drought conditions, accumulate salts and toxic metals, and require minimal maintenance during growth.…”
Section: Comparative Studiessupporting
confidence: 91%
“…Notably, this finding aligns with a previous study that demonstrated approximately threefold variation in glasswort length based on salinity [43]. Hameed et al [44] reported that halophytes have the potential to be used as a sustainable source of food, fuel, feed, fiber, essential oil, and medicine. These hardy plants thrive in high-salinity and drought conditions, accumulate salts and toxic metals, and require minimal maintenance during growth.…”
Section: Comparative Studiessupporting
confidence: 91%
“…Salt-tolerant plants, or halophytes, can thrive in highly saline (≥200 mM sodium chloride) environments, such as salt marshes and coastal dunes. Salinity stress triggers the development of specialised adaptations, including the synthesis of osmolytes (proline, sugars), antioxidative enzymes (superoxide dismutases, catalases, peroxidases), or the synthesis of non-enzymatic antioxidants, crucial for the plant's defence mechanisms and survival [21]. Besides their role in plant welfare, these metabolites also have significant pharmacological potential, including various flavonoids, phenolic acids, and alkaloid derivatives, which are well-documented for their potent antioxidant, anti-inflammatory, and neuroprotective properties [22].…”
Section: Importance Of Salt-tolerant Plantsmentioning
confidence: 99%